Green innovations and organizational change: Making better use of environmental technology - Hanna Hottenrott; Sascha Rexhäuser; Reinhilde Veugelers (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This study investigates productivity effects to firms introducing new environmental technologies. The literature on within-firm organisational change and productivity suggests that firms can get higher productivity effects from adopting new technologies if complementary organisational changes are adopted simultaneously. Such complementarity effects may be of critical importance for the case of adoption of greenhouse gas (GHG) abatement technologies. The adoption of these technologies is often induced by public authorities to limit social costs of climate change, whereas the private returns are much less obvious. We find empirical support for complementarity between green technology adoption and organisational change for a sample of firms located in Germany. The adoption of CO2 reducing and sustainable technologies innovations is associated with lower productivity. The simultaneous implementation of organisational innovations, however, increases the returns to the adoption of green technologies.
Older version: http://hdl.handle.net/10419/60106
Keywords: 330; technical change; environmental innovation; organisational change; productivity